2010
DOI: 10.1159/000260416
|View full text |Cite
|
Sign up to set email alerts
|

Does Pretreatment with Lansoprazole Influence Helicobacter pylori Eradication Rate and Quality of Life?

Abstract: Background/Aims: It is controversial whether pretreatment with a proton pump inhibitor (PPI) before Helicobacter pylori eradication treatment decreases the eradication rate. To determine the effects of pretreatment with lansoprazole alone, followed by an H. pylori eradication regimen (lansoprazole 30 mg, amoxicillin 750 mg and clarithromycin 200 mg twice daily for 1 week), on the eradication rate and quality of life (QoL) of the patient. Methods: Patients with H. pylori-positive peptic ulcer were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Several other authors have reported that the epigastric symptoms and QOL of Hp-positive patients with GERD, FD, and peptic ulcers were significantly improved by the eradication of Hp. [10,11,20] However, these previous studies only evaluated the symptoms and QOL in patients who succeeded with Hp eradication. In contrast, the present study evaluated all patients, regardless of the results of Hp eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Several other authors have reported that the epigastric symptoms and QOL of Hp-positive patients with GERD, FD, and peptic ulcers were significantly improved by the eradication of Hp. [10,11,20] However, these previous studies only evaluated the symptoms and QOL in patients who succeeded with Hp eradication. In contrast, the present study evaluated all patients, regardless of the results of Hp eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with PPI is controversial, and a meta‐analysis showed no differences in eradication rates between patients with or without pretreatment . Some older data suggested that pretreatment with a PPI before the administration of H. pylori eradication therapy might decrease treatment efficacy, but the meta‐analysis and more recent articles do not confirm this information . Given the special circumstances of our patients, we decided that such a strategy, albeit a potential confounding factor, could be beneficial.…”
Section: Discussionmentioning
confidence: 81%
“…The authors theorized that PPIs might induce coccoid-persistent forms of H. pylori , less vulnerable to the antibiotics. Other studies have reported that pretreatment did not affect treatment outcome[32-34]. Inoue et al have reported that there was no statistically significant difference in the eradication rate with the regimen of lansoprazole, amoxicillin and clarithromycin between patients with and without pretreatment (lansoprazole 30 mg, once daily)[32].…”
Section: Pre-treatment With Ppimentioning
confidence: 99%